Acorane sesquiterpenes from the deep-sea derived Penicillium bilaiae fungus with anti-neuroinflammatory effects - Zhang, Wenfang; Meng, Qingyu; Wu, Jingshuai; Cheng, Wei; Liu, Dong; Huang, Jian; Fan, Aili; Xu, Jing; Lin, Wenhan (Frontiers in Chemistry, 2022)
Acorane-type sesquiterpenes comprise an unique class of natural products with a range of pharmaceutical effects. Genome sequencing and gene annotation along with the qRT-PCR detection demonstrate that the deep-sea derived Penicillium bilaiae F-28 fungus is potential to produce acorane sesquiterpenes. Chromatographic manipulation resulted in the isolation of twenty acorane sesquiterpenes from the large-scale fermented fungal strain. Their structures were established by the interpretation of spectroscopic data, together with the X-ray diffraction, chemical conversion, and the ECD data for configurational assignments. A total of 18 new sesquiterpenes namely bilaiaeacorenols A-R (1-18) were identified. Bilaiaeacorenols A and B represent structurally unique tricyclic acoranes. Compound 18 exhibited efficient reduction against the NO production in LPS-induced BV-2 macrophages with a dose-dependent manner, and it abolished LPS-induced NF-κB in the nucleus of BV-2 microglial cells. In addition, the marked reductions of iNOS and COX-2 in protein and mRNA levels were observed. This study extends the chemical diversity of acorane-type sesquiterpenoids, and suggests that 18 is a promising lead for anti-neuroinflammation.